Effects of handwriting exercise on functional outcome in Parkinson disease: A randomized controlled trial - Nisa Vorasoot (2020)
© 2019 Elsevier Ltd Parkinson disease (PD) patients frequently experience micrographia and difficulty writing, which could potentially impact their quality of life. This study aimed to determine whether handwriting exercise could improve fine manual motor function in PD. The study was a randomized controlled trial assessing the efficacy of a 4-week handwriting exercise using a newly developed handwriting practice book. The primary endpoint was an improvement in the time used to complete the handwriting test. Secondary endpoints were accuracy of the writing performance, patient's subjective rating scale of their handwriting and a UPDRS part III motor examination. Of a total of 46 subjects, 23 were randomly assigned to the handwriting exercise group. After 4 weeks, the mean time used to complete the test was significantly lower in the exercise group, compared to the control group (143.43 ± 34.02 vs. 175 ± 48.88 s, p = 0.015). Mean time used to complete the handwriting test decreased from the baseline by 16.16% in the exercise group, but increased by 3.63% in the control group (p < 0.001). Significant improvements were also observed by assessing the subjective rating scale and the UPDRS part III scores. The 4-week handwriting exercise using the studied handwriting practice book appears to promote an improvement in writing speed and motor function of hands. The optimal duration and frequency of the exercise, the quantity and characteristic of the letters in the handwriting practice book, and the benefits of the exercise in other languages merit further studies.